The economy today - Schiller, Bradley R., 1943- (New York : McGraw-Hill, 1991)
The Economy Today responds fully to the challenges of the collapse of communism while market and command economies are compared throughout the text, in areas as diverse as commodity pricing, labor relations, environmental protection, and trade.
Includes index.
rua 04/05/15
Loans
Keywords: Economics